Tinjauan Literatur Tentang Faktor-Faktor yang Mempengaruhi Perilaku Remaja terhadap Penggunaan Rokok Elektrik (Vape) dalam Perspektif Teori Sosial Kognitif - Annisa Zahria Putri Handayani; Luqman Effendi (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The use of electronic cigarettes (vapes) among adolescents continues to increase and has emerged as a significant public health concern influenced by the interaction of individual, social, and environmental factors. This study aims to comprehensively riview the factors influencing adolescent e-cigarette use from the perspective of Social Cognitive Theory. A descriptive-narrative literature review was conducted using empirical national and international studies published between 2015 and 2025 and retrieved from Google Scholar, PubMed, and ScienceDirect databases. The synthesis of the literature indicates that adolescent vaping behavior is influenced by social environmental factors, including peer influence and exposure to social media, as well as personal cognitive factors such as knowledge, risk perception, outcome expectations, and self-efficacy. These factors operate thorugh observational learning and reciprocal interactions between individuals, environment, and behavior. This review concludes that Social Cognitive Theory provides a relevant and comprehensive framework for understanding adolescent vaping behavior and offers a foundations for the development of effective health promotion interventions and preventive policies.